(untitled) (CIPEEX, 2025)
The present study aimed to observe the evolution of sarcopenic volunteers, as well as to demonstrate the efficiency of PEMF – a therapy that uses low-frequency pulsed electromagnetic fields. Initially, the volunteers were evaluated, and in subsequent sessions, resistance exercises were performed to strengthen the upper limbs (UL), while for the lower limbs, only the Supramaximus equipment was used, with the handholds positioned on the rectus femoris and gastrocnemius muscles. The volunteers underwent the Time Up and Go (TUG) test at the first and last consultations to check the participants’ functional mobility and balance. After analyzing the data, significant improvements were observed both in TUG test results and in patients’ quality of life. Although some volunteers did not show a statistically significant response during the tests, they reported satisfactory results in their daily activities. It was concluded that the use of electromagnetic fields in the treatment of sarcopenia is effective.